Authentication of Cyathulae Radix and Cyathulae Capitatae Radix based on the strength of the characteristic component achybidensaponin I. (10th November 2022) - Ma, Yanhong; Gao, Bixing; Qi, Jingliang; Gou, Yan; Li, Zhi; Chen, Yingxin; Li, Min; Zhou, Juan; Zhong, Lian; Cai, Xiaoyang
Abstract: Because of the immense difficulty in identifying Cyathulae Capitatae Radix adulteration in Cyathulae Radix, this research aims at fortifying the quality control of Cyathulae Radix and its decoction pieces to guarantee the effectiveness and safety of its clinical use in terms of source material. A method was devised to identify Cyathulae Capitatae Radix adulteration in Cyathulae Radix and its decoction pieces. This research takes achybidensaponin I, that is, the characteristic component of Cyathulae Capitatae Radix, as reference substance and adopts HPLC for detection. The results revealed that, among all samples collected, no trace of achybidensaponin I was found in the 21 batches of Cyathulae Radix, whereas achybidensaponin I was found in all the 14 batches of Cyathulae Capitatae Radix. The research sets 5% as the adulteration limit, that is, 1.45 mg/g Cyathulae Capitatae Radix was detected in 57.14% of the 49 batches of market samples collected and the ratio was 51.02% in the case of 5% adulteration limit. The method is not only precise and reliable but can also be used as a supplement for provisions regarding quality control of Cyathulae Radix and its decoction pieces in Pharmacopoeia of the People's Republic of China, to effectively crack down on Cyathulae Capitatae Radix adulteration in the market.